2020
DOI: 10.3390/microorganisms8010139
|View full text |Cite
|
Sign up to set email alerts
|

Dietary Factors as Triggers of Low-Grade Chronic Intestinal Inflammation in Poultry

Abstract: Inflammation is the reaction of the immune system to an injury; it is aimed at the recovery and repair of damaged tissue. The inflammatory response can be beneficial to the animal since it will reestablish tissue homeostasis if well regulated. However, if it is not controlled, inflammation might lead to a chronic response with a subsequent loss of tissue function. The intestine is constantly exposed to a number of environmental triggers that stimulate inflammation and lead to a reduction in performance. The di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(29 citation statements)
references
References 89 publications
(119 reference statements)
0
20
0
3
Order By: Relevance
“…The diets were based on corn and soybean meal and formulated to meet or exceed the nutritional levels from the starter phase ( Cobb Vantress, 2018b ) for all ingredients, except for Arg ( Table 1 ). It is believed that changes in feed formulation, for example feed ingredients and nutritional levels, could be a source of inflammation in the gastrointestinal tract ( Kogut et al., 2018 ; Cardoso Dal Pont et al., 2020 ). To avoid a potential influence of the basal diet on the intestinal health status, the same nutritional level was used from 1 to 26 d. The dietary treatments were determined by formulating an Arg deficient diet, without Arg supplementation (1.04%), and adding Arg as a replacement of the inert component (sand) to reach equidistant calculated levels below and above the Cobb 500 recommendation (1.24%).…”
Section: Methodsmentioning
confidence: 99%
“…The diets were based on corn and soybean meal and formulated to meet or exceed the nutritional levels from the starter phase ( Cobb Vantress, 2018b ) for all ingredients, except for Arg ( Table 1 ). It is believed that changes in feed formulation, for example feed ingredients and nutritional levels, could be a source of inflammation in the gastrointestinal tract ( Kogut et al., 2018 ; Cardoso Dal Pont et al., 2020 ). To avoid a potential influence of the basal diet on the intestinal health status, the same nutritional level was used from 1 to 26 d. The dietary treatments were determined by formulating an Arg deficient diet, without Arg supplementation (1.04%), and adding Arg as a replacement of the inert component (sand) to reach equidistant calculated levels below and above the Cobb 500 recommendation (1.24%).…”
Section: Methodsmentioning
confidence: 99%
“…Mycotoxins are considered as major nutritional stress factors in poultry production [ 1 ] imposing oxidative stress, immunosuppression [ 207 ], and low-grade inflammatory response in the chicken intestine [ 44 ] and compromising intestinal barrier functions [ 208 ]. Among feed-contaminating mycotoxins, AFB1 is considered to be the most toxic mycotoxin.…”
Section: Effect Of Various Stress Factors On Nf-κb Expression and mentioning
confidence: 99%
“…It was hypothesized that subclinical gut disorders leading to a chronic low-level inflammatory response in the gut associated with oxidative stress and redox disbalance could result in the disruption of digestive function and poor immune competence [ 44 ]. Furthermore, the authors also suggested that chronic intestinal inflammation is responsible for the decreased performance and increased incidence of intestinal problems observed in poultry production.…”
Section: Nf-κb and Inflammation In Poultry Productionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although inflammation is a fundamental process to fight infection, prolonged and chronic inflammation leads to damaging consequences such as tissue and organ damage, and mortality ( 2 ). In livestock farming, numerous factors induce the occurrence of inflammation, including the intensification of production, poor quality, and contamination in feedstuffs as well as genetic selection ( 7 ). As a result, this will contribute to poor growth performance and production due to low nutrient absorption, loss of appetite, impaired intestinal architecture, and leaky gut ( 4 , 8 ), which lead to a large amount of energy consumption on the immune system instead of growing and production ( 9 ).…”
Section: Introductionmentioning
confidence: 99%